ACHIEVEMENTS AND PROBLEMS OF ELECTRODE MODIFICATION FOR VOLTAMMETRY - Narmaeva, Gavkhar; Aronbaev, Sergei; Aronbaev, Dmitry (International Journal of Research -GRANTHAALAYAH, 2018)
In a review article, the achievements and problems of modifying carbon-containing electrodes for voltammetric analysis are considered. Various methods for chemical modification of electrodes are described, including methods of surface modification, volumetric modification, impregnation by in-situ and ex-situ methods. It is noted that modified electrodes with a catalytic response are increasingly used in voltammetry. This is explained by the fact that in a number of cases the catalytic currents that are caused by the included or previous chemical reaction far exceed the limiting diffusion currents, which makes it possible to increase the sensitivity of the method and to lower the lower limit of the determination by several orders of magnitude. Examples of the use of chemically modified carbon-containing electrodes in the voltammetric analysis of inorganic ions and organic substances are given.